Depressive rumination and heart rate variability: A pilot study on the effect of biofeedback on rumination and its physiological concomitants - Schumann, Andy; Helbing, Nadin; Rieger, Katrin; Suttkus, Stefanie; Bär, Karl-Jürgen (Frontiers in Psychiatry, 2022)
Objective Recent studies suggest that lower resting heart rate variability (HRV) is associated with elevated vulnerability to depressive rumination. In this study, we tested whether increases in HRV after HRV-biofeedback training are accompanied by reductions in rumination levels. Methods Sixteen patients suffering from depression completed a six-week HRV-biofeedback training and fourteen patients completed a control condition in which there was no intervention (waitlist). The training included five sessions per week at home using a smartphone application and an ECG belt. Depressive symptoms and autonomic function at rest and during induced rumination were assessed before and after each of the two conditions. We used a well-established rumination induction task to provoke a state of pervasive rumination while recording various physiological signals simultaneously. Changes in HRV, respiration rate, skin conductance, and pupil diameter were compared between conditions and time points. Results At significant correlation was found between resting HRV and rumination levels, both assessed at the first laboratory session (r=-0.43, p<0.05). Induction of rumination led to an acceleration of heart rate and skin conductance increases. After biofeedback training, resting vagal HRV was increased (p<0.01) and self-ratings of state anxiety (p<0.05), rumination (p<0.05), perceived stress (p<0.05), and depressive symptoms (QIDS, BDI; both p<0.05) were decreased. In the control condition, there were no changes in autonomic indices or depressive symptomatology. A significant interaction effect group x time on HRV was observed. We found no significant effect of biofeedback on self-reported rumination levels. Conclusions Our results indicate that a smartphone-based HRV-biofeedback intervention can be applied to improve cardiovagal function and to reduce depressive symptoms including self-rated rumination tendencies.